The Effect Of Transfer Funds And Regional Original Income (Pad) On Poverty Levels In Regencies/Cities Of North Sumatra Province - Muhardinata, Muhardinata; Erlina, Erlina; Rujiman, Rujiman (Publisher Cv. Inara, 2022)
The objectives of this study are to: 1. Analyze the effect of Regional Original Income on the level of poverty in the Regency/City of North Sumatra Province. 2. Analyzing the effect of the General Allocation Fund on the poverty level in the Regency/City of North Sumatra Province. 3. Analyzing the effect of the Special Allocation Fund on the poverty level in the Regency/City of North Sumatra Province. 4. Analyzing the effect of the Revenue Sharing Fund on the poverty level in the Regency/City of North Sumatra Province. 5. Analyzing the effect of the General Allocation Fund, Special Allocation Fund, Revenue Sharing Fund, and Regional Original Income together on the poverty level in the Regency/City of North Sumatra Province. The method used is multiple linear analysis. The results in this study are 95.22 percent of the variation that occurs in the dependent variable can be explained by the independent variable. The remaining 4.78 percent is explained by other variables not used in the study such as inflation, economic growth, and unemployment; The DAU variable does not significantly affect the poverty level, the probability value of X2 is 0.0813 > 0.05, indicating that the DAK variable has no significant effect on the poverty level, the X3 probability value is 0.3698 > 0.05, indicating that the DBH variable has no significant effect. on the poverty level, and the probability value of X4 in the table is 0.6903 > 0.05, which indicates that the PAD variable has no significant effect on the poverty level; The significance of the simultaneous test that describes the effect of X1 (PAD), X2 (DAU), X3 (DAK), and X4 (DBH) together can be seen in Table 4.8 precisely on the value of Prob. (F-statistic) which is 0, 0000 < 0.05. This value shows that PAD, DAU, DAK, and DBH together have a significant effect.